Bahelena lemat be Ethiopia : be Forem for social studies yaweyeyet madrak lay yaqarabu tenatawi tehufoch - Shiferaw Bekele (Adiss Ababa, Ethiopia : Forum for Social Studies, 2004)
Culture and development oriented research articles presented at FSS discusion forum in Ethiopia.
Includes bibliographical references (p. [241]-249)
In Amharic.
Keywords: Culture and development